The Infuences of moral judgment, social influence and attitude on non-deceptive behavior - Nor Azila, Mohd Noor,; Azli, Muhammad,; Lum Li, Sean, (Opción, 2019)
This study examines the factors influencing consumers’ nondeceptive purchase behavior of counterfeit products. A selfadministered questionnaire was designed using established scales. This study utilized PLS-SEM to establish the validity and reliability of the measurement model and to test the hypotheses. The outcomes of this study show that non-deceptive purchase behavior of counterfeit products is positively been influenced by attitude and social influence, while moral judgment negatively influences non-deceptive purchase behavior of counterfeit products among consumers. In conclusion, different categories of counterfeit products may have a different effect on the purchase behavior of the consumers.